An Overview of Nucleic Acid Testing for the Novel Coronavirus SARS-CoV-2 - Wang, Huiling; Li, Gang; Zhao, Jing; Li, Yanjie; Ai, Yushu (Frontiers in Medicine, 2021)
The novel coronavirus pneumonia (COVID-19) pathogen is severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Viral NAT (nucleic acid testing) is a rapid approach for detecting and diagnosing SARS-CoV-2 infection. NAT is considered the diagnostic gold standard; however, NAT has generated many false-negative results, affecting early diagnosis of the disease and interfering with the mitigation and containment of the pandemic. There are several problems with SARS-CoV-2 NAT: 1. The specificity and accuracy of NAT needs to be improved. 2. There are numerous procedures for the detection of nucleic acids. 3. It is difficult to control the timing of the specimen collection. 4. Selection of body sites for specimen collection needs to be optimized. We have suggestions for the integration of NAT into the diagnosis: 1. Serological indicators should be combined with NAT results for a comprehensive evaluation. 2. Specimen collection methods and processes should be standardized. 3. Testing reagents should be subjected to more rigorous supervision and approval procedures. 4. Dynamic changes in chest CT images should be considered when evaluating the disease progression. In conclusion, comprehensive analysis of serological and imaging findings should be performed to formulate an accurate clinical diagnosis and design a treatment plan.